Effectiveness of different treatment regimens on patients with COVID-19, hospitalized in Sanandaj hospitals: a retrospective cohort study - Jalal Asadi; Mohammad Aziz Rasouli; Ebrahim Ghaderi; Daem Roshani; Behzad Mohsenpour; Yousef Moradi; Ghobad Moradi (Taylor & Francis Group, 2023)
Abstract Objectives Different drugs have different effects on the prognosis of patients with COVID-19. This study aimed to evaluate the effect of different drug regimens on patients with COVID-19, hospitalized in Sanandaj city. Methods In this retrospective cohort study, 660 patients with COVID-19, hospitalized in the Tohid, Kowsar and Besat hospitals located Sanandaj (Kurdistan Province, Iran) were studied from February 2020 to February 2021 with clinical symptoms and positive test results. Results The results of multivariate regression analysis showed the days of hospitalization for patients who had received the drug regimen 2 (Interferons (ReciGen/Ziphron) or Interferon Vectra (lopinavir/ritonavir)) was 1.92 times higher than those who had received the drug regimen 1 (hydroxychloroquine group or a combination of chloroquine and azithromycin) while a significant association was observed (OR = 1.92, 95% CI: 1.16-3.16, P = 0.011). Also, the hospitalization in ICU was longer in patients treated by the drug regimen 2 (Interferons (ReciGen/Ziphron) or Interferon Vectra (lopinavir/ritonavir)) (OR = 4.63, 95% CI: 1.80-11.82, P = 0.001), however, drug regimens did not show a significant effect on mortality and use of ventilator in patients (P > 0.05). Conclusion The study results showed the drug regimens 2 and 5 increased the days of hospitalization and hospitalization in ICU, respectively, while the other drug regimens had no significant effect on mortality and use a ventilator in the studied patients and none of the drug regimens had an effect on reducing mortality compared to other ones.